1996
DOI: 10.1177/000348949610501005
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatization of the Tympanic Bulla after Blockage of the Ventilation Route through the Eustachian Tube in the Pig

Abstract: To examine whether gas exchange occurs in the middle ear air cell system independent of the eustachian tube (ET), we occluded the middle ear clefts of piglets, whose tympanic bullae closely resemble the human mastoid air cell system, and investigated subsequent changes in the air cell system. We anticipated that pneumatization and development of the air cell system would continue if gas were exchanged through the mucosa lining the air cell system. If, on the other hand, mastoid air cells depend on the ET, mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Gas exchange across the mastoid air cell mucosa has been documented in the previous studies (12Y15). The pneumatization is symmetrical in 72% to 99% of the general population (19,20). The nonpneumatized bony parts compose of bone marrowYcontaining areas (in the diploic mastoid) and dense bone (in the sclerotic mastoid) (1).…”
Section: Discussionmentioning
confidence: 99%
“…Gas exchange across the mastoid air cell mucosa has been documented in the previous studies (12Y15). The pneumatization is symmetrical in 72% to 99% of the general population (19,20). The nonpneumatized bony parts compose of bone marrowYcontaining areas (in the diploic mastoid) and dense bone (in the sclerotic mastoid) (1).…”
Section: Discussionmentioning
confidence: 99%
“…It is through this mucosa that mastoid air cell functions such as gas exchange, material secretion, waste excretion, and the maintenance of middle ear cavity aeration occur. Blood capillaries are abundant in the mastoid mucosa and function in gas exchange according to concentration or pressure gradients, much like the alveolar gas exchange mechanism found in the lungs 2–7 . In other words, the mastoid cavity is not only an air reservoir but also an active surface area for gas exchange.…”
Section: Discussionmentioning
confidence: 99%
“…This structural feature is intimately associated with their physiologic functions. Recent studies have revealed that mastoid air cells, because of the gas exchange function of their mucosa, play an important role in pressure regulation of the middle ear 1–7 . Failure of this function precludes good aeration of the middle ear cavity.…”
Section: Introductionmentioning
confidence: 99%
“…It is also common in birds for distinct diverticular networks to anastomose with one another, such that those pneumatizing neural arches are continuous with those of the centra. The exact mechanism by which pneumatic diverticula induce bone resorption and interact with one another within a given bone requires further study (e.g., Bremer, 1940b;Ikarashi et al, 1996;Hönig et al, 2002).…”
Section: Osteological Correlates Of Different Soft-tissue Systemsmentioning
confidence: 99%